Tumour necrosis factor-alpha in infectious meningitis. Issue 9 (September 1989) - Nadal, D; Leppert, D; Frei, K; Gallo, P; Lamche, H; Fontana, A
Abstract : During a one year period tumour necrosis factor-alpha (TNF-alpha) was prospectively determined in the cerebrospinal fluid of 49 patients with infectious meningitis. TNF-alpha was found in the cerebrospinal fluid of 15 of 18 patients with bacterial meningitis. In 11 patients who had cerebrospinal fluid positive for TNF-alpha it was detected in only one serum (in low concentration). There was no significant correlation between the concentration of TNF-alpha in cerebrospinal fluid and the patient's age, duration of illness and fever, body temperature, and serum C reactive protein. However, cerebrospinal fluid protein concentrations of greater than or equal to 2 g/l and leucocyte values of greater than or equal to 2.5 X 10(9)/l were more often associated with high TNF-alpha concentrations (greater than or equal to 500 pg/ml). In contrast with bacterial meningitis, none of the 31 samples of cerebrospinal fluid from patients with viral meningitis was positive for TNF-alpha. Thus this investigation supports the conclusion, drawn from animal studies on TNF-alpha in the cerebrospinal fluid, that the presence of TNF-alpha is indicative of bacterial meningitis. Absence of TNF-alpha cerebrospinal fluid, however, was found here not to exclude a bacterial aetiology of the infection.